The namesake - Lahiri, Jhumpa (New York : b)
Tells the story of a boy brought up as an Indian in suburban America, Gogol Ganguli, who soon finds himself itching to cast off his awkward name, just as he longs to leave behind the inherited values of his Bengali parents. And so, he sets off on his own path through life, a path strewn with conflicting loyalties, love and loss.
Keywords: Young men -- Fiction; East Indian Americans -- Fiction; Children of immigrants -- Fiction; Assimilation (Sociology).; Alienation (Social psychology).